Simulation of Deposition the Corrosion Waste in a Water Distribution System - Jeleníková, Ivana; Šikula, Ondřej; Peráčková, Jana (EDP Sciences, 2013)
In water distribution systems can be found particles of rust and other mechanical contaminants. The particles are deposited in locations where the low velocity of water flow. Where a can cause the pitting corrosion. Is a concern in the systems made of galvanized steel pipes. The contribution deals with CFD (Computational Fluid Dynamics) simulations of water flow and particles deposition in water distribution system. CFD Simulations were compared with the corrosive deposits in real pipeline. Corrosion is a spontaneous process of destruction of metal material due to electrochemical reactions of metal with the aggressive surrounding. Electrochemical corrosion is caused by the thermodynamic instability of metal and therefore can not be completely suppress, it can only influence the speed of corrosion. The requirement is to keep metal properties during the whole its lifetime. Requested service lifetime the water pipe according to EN 806-2 is 50 years.

In water distribution systems can be found particles of rust and other mechanical contaminants. The particles are deposited in locations where the low velocity of water flow. Where a can cause the pitting corrosion. Is a concern in the systems made of galvanized steel pipes. The contribution deals with CFD (Computational Fluid Dynamics) simulations of water flow and particles deposition in water distribution system. CFD Simulations were compared with the corrosive deposits in real pipeline. Corrosion is a spontaneous process of destruction of metal material due to electrochemical reactions of metal with the aggressive surrounding. Electrochemical corrosion is caused by the thermodynamic instability of metal and therefore can not be completely suppress, it can only influence the speed of corrosion. The requirement is to keep metal properties during the whole its lifetime. Requested service lifetime the water pipe according to EN 806-2 is 50 years.
Simulation of Deposition the Corrosion Waste in a Water Distribution System
Keywords: water distribution system; corrosion; sedimentation; cfd (Computational Fluid Dynamics) simulation; water distribution system; corrosion; sedimentation; cfd (Computational Fluid Dynamics) simulation